Analisis Kinerja Perusahaan CV. Bali Indah dengan Metode Balanced Scorecard - Saraswati, PS.; Darmawan, DP.; Suamba, K (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2017)
ABSTRACT ANALYSIS OF COMPANY PERFORMANCE OF CV. BALI INDAH WITH BALANCED SCORECARD METHOD Business competition has raised the work standard in various dimensions such as quality, cost, and smooth operation. The challenge caused by the increasing competition is that companies or institutions will do anything that is considered important for strategic competitiveness and overall business improvement. That is, companies will always compete to attract customers by offering various facilities at competitive prices. This situation will obviously encourage the management to make certain strategies in order to win the competition and achieve companies ultimate goals. This study entitled "Analysis of Company Performance of CV. Bali Indah with Balanced Scorecard method. The company's performance is looked from four perspectives of Balanced Scorecard namely financial perspective, customer, internal business processes, learning and growth. The aim of this study is to analyze the performance of CV. Bali Indah based on the four perspectives of the Balanced Scorecard. The Performance of CV. Bali Indah from a financial perspective in this study were assessed using Liquidity Ratio (current ratio and quick ratio), Profitability Ratio (net profit margin, return on assets and return on equity), Solvency Ratio (total asset to debt ratio and networth to debt ratio), Leverage ratio (total debt total assets ratio and total debt to equity ratio) and Activity Ratio (total assets turn over). The performance of costumer perspective used the customer acquisition and customer satisfaction index. Internal business process performance was assessed by using Manufacturing Cycle Effectiveness (MCE). The performance assessment of learning and growth perspective was done by assessing the capability of employees by measuring employee productivity and employee satisfaction index. Based on the study findings, it can be concluded that CV. Bali Indah from Financial Perspective of the year 2011-2014 is rated good. From the customer perspective, customer acquisition fluctuated and customer satisfaction index results arevery good (customers were satisfied with their transactions with CV. Bali Indah). Assessment on internal business process perspective by assessing product order transaction using Cycle Manufacturing Effectiveness is rated good. Product ordertransaction has run effectively.In term of learning and growth perspective, employee productivity fluctuated from 2011-2014 and the employee satisfaction index result is good (employees are satisfied with their employment in CV. Bali Indah) Key Words: Balanced Scorecard, Financial Perspective, Customer Perspective, Internal Business Process Perspective and Learning and Growth Perspective.